SAT0455 Clinical and immunological characteristics of patients with suspected sjÖgren syndrome and anti-ro52 positive antibodies. (12th June 2018) - Solans-Laque, R.; Loureiro, J.; Marin, A.; Martinez-Valle, F.; Alberola, M.; Puig, J.J.; Mestre, J.; Bujan, S.
Abstract : Background: Anti-Ro52 antibodies have been described in patients with Sjögren syndrome (SS) but there are limited data on their significance, and they are not included in the diagnostic criteria of SS. Objectives: To analyse the clinical and immunological characteristics of patients with suspected SS and positive anti-Ro52 antibodies, and to assess the diagnostic value of this antibodies. Methods: retrospective study of all patients evaluated at our Department between January 2000 and January 2016 for possible SS in which anti-Ro52 abs. were determined. Patients were classified as having SS, according to the 2002 European-American Consensus Group (EACG) criteria. Statistical analysis was performed using the SPSS vs.20 package Results: 348 patients (331 women), mean age at diagnosis 56.12±14.19 years (range 22–92), with possible SS were analysed. All patients met the European criteria for SS diagnosis, and 242 the EACG criteria. AAN were positive in 345 (99.4%) patients, RF in 169 (48.4%), anti-Ro60/SSA in188 (54%), and anti-La/SSB in 11 (32%). Anti-Ro52 abs. were positive in 173 (49.7%) patients: 162 women, 11 men. Of these patients, 154 (89%) also had anti-Ro60/SSA positive abs., 103 (59.5%) anti-La/SSB abs., and 117 (67.6%) positive RF. Anaemia, leukopenia, lymphocytopenia and hypergammaglobulinemia, were significantly more frequent in patients with anti-Ro52 positive abs. The presence of anti-Ro52 abs. was significantly related to the development of lung fibrosis (OR 2.42, 95% CI 1.23–4.75, p=0.007), peripheral neuropathy (OR 2.53, 95% CI 1.1–5.95, p=0.022), arthritis (OR 1.95, 95% CI 1.2–3.35, p=0.016) and parotitis (OR 3.04, 95% CI 1.75–5.3, p<0.001). A total of 160/173 (92.5%) patients with anti-Ro positive abs. met the EACG criteria. When we analysed the 13 patients with anti-Ro52 positive abs., which did not meet the AECG criteria, these patients presented severe salivary gland scintigraphic involvement, positive ocular test for dry eyes, more hypergammaglobulinemia (OR 6.67, 95% CI 1.95–22.8, p=0.003), more peripheral neuropathy (OR 13.8, 95% CI 2.1–92.7, p=0.0012), more lung fibrosis (OR 13.95, 95% CI 2.1–93.7, p=0.012), and more risk of lymphoma development (OR 16.72, 95% CI 1.4–199.8, p=0.039), than patients with suspected SS who did not met the AECG criteria and who had negative anti-Ro52 abs. Conclusions: in our series most patients with anti-Ro52 positive antibodies had also anti-Ro60/SSA positive antibodies and met the AECG criteria. However, there were 13 patients with positive anti-Ro52 abs., which did not meet the AECG criteria. These patients showed similar characteristics to those with positive anti-Ro52 abs. and AECG criteria, and had more risk to develop peripheral neuropathy, lung fibrosis and lymphoma. Our results support that anti-Ro52 antibodies should be included in the diagnostic criteria for SS. Disclosure of Interest: None declared